The Biodiversity Informatics Landscape: Elements, Connections and Opportunities - Heather Bingham; Michel Doudin; Lauren Weatherdon; Katherine Despot-Belmonte; Florian Wetzel; Quentin Groom; Edward Lewis; Eugenie Regan; Ward Appeltans; Anton Güntsch; Patricia Mergen; Donat Agosti; et al. (Research Ideas and Outcomes, 2017)
There are a multitude of biodiversity informatics projects, datasets, databases and initiatives at the global level, and many more at regional, national, and sometimes local levels. In such a complex landscape, it can be unclear how different elements relate to each other. Based on a high-level review of global and European-level elements, we present a map of the biodiversity informatics landscape. This is a first attempt at identifying key datasets/databases and data services, and mapping them in a way that can be used to identify the links, gaps and redundancies in the landscape. While the map is predominantly focused on elements with a global scope, the sub-global focus at the European-level was incorporated in the map in order to demonstrate how a regional network such as the European Biodiversity Observation Network (EU BON) can usefully contribute to connecting some of the nodes within the landscape. We identify 74 elements, and find that the informatics landscape is complex in terms of the characteristics and diversity of these elements, and that there is high variability in their level of connectedness. Overall, the landscape is highly connected, with one element boasting 28 connections. The average "degrees of separation" between elements is low, and the landscape is deemed relatively robust to failures since there is no single point that information flows through. Examples of possible effort duplication are presented, and the inclusion of five policy-level elements in the map helps illustrate how informatics products can contribute to global processes that define and direct political targets. Beyond simply describing the existing landscape, this map will support a better understanding of the landscape’s current structure and functioning, enabling responsible institutions to establish or strengthen collaborations, work towards avoiding effort duplication, and facilitate access to the biodiversity data, information and knowledge required to support effective decision-making, in the context of comparatively limited funding for biodiversity knowledge and conservation. To support this, we provide the input matrix and code that created this map as supplementary materials, so that readers can more closely examine the links in the landscape, and edit the map to suit their own purposes.